The Effect of Shadow Play on Preschool Children's Fundamental Movement Skills - Malihe Rezae; Maryam Nezakatalhosseini; Rokhsareh Badami (University of Tehran, 2017)
The aim of this study was to investigate the effect of 10 weeks of shadow play on preschool children's fundamental movement skills. In this quasi-experimental study with pretest/posttest design and a control group, 28 girls and boys (6 years old) were selected by convenience sampling method from children in a preschool and were randomly divided into the experimental group (5 girls & 9 boys) and the control group (5 girls & 9 boys). For 10 weeks (three 45-minute sessions), the experimental group performed the shadow play and the control group had their routine activities of preschool. The pretest and the posttest were administered by "the Movement Assessment Battery for Children-Test (M-ABC)". This test consisted of three subtests of manual dexterity, ball skills and balance skills. Analysis of data was performed by covariance analysis (α=0.05). The results showed that 10 weeks of shadow play had a significant effect on subtests of manual dexterity, balance skills and the total score of fundamental skills but had no significant effects on ball skills. Findings of this study showed that shadow play may improve preschool children's fundamental movement skills.